Investigation on Newcastle Disease Virus (NDV), Infectious Bursal Disease Virus (IBDV) and Avian Poxvirus (APV) in magellanic penguins in Southern region of Brazil - Cristina Freitas Nunes; Fabiane Fonseca; Alice Teixeira Meirelles Leite; Rodolfo Pinho da Silva Filho; Paula Fonseca Finger; Clarissa Caetano Castro; Geferson Fischer; Gilberto D'avila Vargas; Silvia de Oliveira Hübner (Brazilian Archives of Biology and Technology, 2012)
To investigate the exposure of the Newcastle disease virus (NDV), infectious bursal disease virus (IBDV) and avian poxvirus (APV) in Magellanic penguins found on the beaches in Southern regions of Brazil, the frequency of serum antibodies was estimated in 89 samples taken during 2005 and 2006. All the penguins were negative for the presence of antibodies against NDV by hemagglutination inhibition test and to APV by indirect ELISA. The reactivity was similar to the positives controls using ELISA kit for the IBDV made in the chickens in 50 samples. This reactivity also was demonstrated in 42 samples using agar gel immunodiffusion. No clinical signs related to IBDV infection were observed. The results indicated the absence of infection by NDV and APV but suggested IBDV exposure in the population of penguins studied.